Inhibition of prolyl 4-hydroxylase, beta polypeptide (P4HB) attenuates temozolomide resistance in malignant glioma via the endoplasmic reticulum stress response (ERSR) pathways - Sun, Stella (Oxford University Press, 2013)
BACKGROUND: Glioblastoma multiforme (GBM), the most aggressive malignant primary brain tumor of the central nervous system, is characterized by a relentless disease recurrence despite continued advancement in surgery, radiotherapy, and chemotherapy. Resistance to temozolomide (TMZ), a standard chemotherapeutic agent for GBM, remains a major challenge. Understanding the mechanisms behind TMZ resistance can direct the development of novel strategies for the prevention, monitoring, and treatment of tumor relapse. METHODS AND RESULTS: Our research platform, based on the establishment of 2 pairs of TMZ-sensitive/resistant GBM cells (D54-S and D54-R; U87-S and U87-R), has successfully identified prolyl 4-hydroxylase, beta polypeptide (P4HB) over-expression to be associated with an increased IC(50) of TMZ. Elevated P4HB expression was verified using in vivo xenografts developed from U87-R cells. Clinically, we found that P4HB was relatively up-regulated in the recurrent GBM specimens that were initially responsive to TMZ but later developed acquired resistance, when compared with treatment-naive tumors. Functionally, P4HB inhibition by RNAi knockdown and bacitracin inhibition could sensitize D54-R and U87-R cells to TMZ in vitro and in vivo, whereas over-expression of P4HB in vitro conferred resistance to TMZ in both D54-S and U87-S cells. Moreover, targeting P4HB blocked its protective function and sensitized glioma cells to TMZ through the PERK arm of the endoplasmic reticulum stress response. CONCLUSIONS: Our study identified a novel target together with its functional pathway in the development of TMZ resistance. P4HB inhibition may be used alone or in combination with TMZ for the treatment of TMZ-resistant GBM.